Determinan Kinerja Akuntan Internal dengan Self Efficacy sebagai Pemoderasi - Lia Juniawati; M. Irfan Tarmizi (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to determine the effect of competence, work motivation, leadership style, and compensation on the performance of internal accountants partially, with self-efficacy as a moderating variable. The data used in this study is primary data, namely through questionnaires on seven service companies in the South Jakarta area. Sampling using convenience sampling method. This test uses the SPSS Version 22 program with hypothesis testing through t-test (partial/individual) and MRA (Moderated Regression Analysis). The results of this study partially show that competence, leadership style, compensation, and self-efficacy have a significant effect on the performance of internal accountants. While work motivation has no effect on the performance of internal accountants. Self-efficacy can weaken the influence of competence, work motivation, and leadership style on the performance of internal accountants. Meanwhile, self-efficacy strengthens the effect of compensation on the performance of internal accountants. This research is in accordance with the theory of expectation, namely that someone will take an action according to his knowledge and abilities. The same applies to the theory of planned behavior and Maslow's hierarchy of needs theory. An employee will be motivated to do what he wants, one of which is compensation. Compensation is one way to meet daily needs.